Analisis Faktor Penyebab Rendahnya Kemampuan Literasi Sains Peserta Didik Pada Mata Pelajaran IPAS Kelas V Sekolah Dasar - Suri, Mara Anna Odilia; Naitili, Cornelia Amanda; Nitte, Yulsy Marselina (Universitas Pahlawan Tuanku Tambusai, 2025)
Education is a process that aims to optimize individual potential through programmed learning experiences, whether formal, non-formal, or informal, that continue throughout life. The purpose of this study is to identify the factors that influence science literacy skills in IPAS subjects and to determine efforts to overcome low science literacy skills in IPAS subjects. This study employs a qualitative research approach using a descriptive methodology conducted at SDK St. Yoseph 1 Naikoten Kupang, with research subjects including the school principal, classroom teachers, and students. Data collection techniques include interviews, observations, and document analysis. The research findings indicate that the factors contributing to low science literacy skills in the IPAS subject are internal factors, including: low student interest in learning, low student motivation to learn, low student intellectual ability, and psychological health factors. External factors include: curriculum and education system, low teacher teaching methods and models, limited learning resources and teaching materials, teacher quality and school management, learning environment outside of school, library and school facilities conditions, and limited learning facilities and infrastructure. Given the factors influencing low science literacy as mentioned above, efforts are needed to address this issue, both from within the students (internal) and from external sources such as teachers and school principals. However, in reality, there are no efforts from students, teachers, or school principals to address this issue. Therefore, this study concludes that the low science literacy among students can be influenced by internal and external factors, necessitating efforts to address science literacy in the IPAS subject, including efforts from within (internal) and from outside (external) involving teachers and school principals.